Chemical constituents of essential oils of Boesenbergia armeniaca and B. stenophylla (Zingiberaceae) endemic to Borneo - Nor, Norlailatul Asikin Mohamad; Ibrahim, Halijah (Pakistan Botanical Society, 2018)
Boesenbergia armeniaca and B. stenophylla are two endemic wild gingers from Borneo. Limited information are available on these wild species. The aim of this study was to identify the leaf essential oil constituents using hydrodistillation and analysed via GC-FID and GC-MS. The essential oil yields of leaves obtained from B. armeniaca and B. stenophylla were 0.01% and 0.08% respectively. The leaf oil of B. armeniaca was dominated by oxygenated sesquiterpenes (47.95%), while the leaf oil of B. stenophylla was dominated by oxygenated monoterpenes (85.12%). The main volatile constituents in the leaf oil of B. armeniaca were Nerolidol (42.55%), Linalool (11.63%) and β-caryophyllene (6.25%) while in the leaf oil of B. stenophylla, methyl cinnamate (83.17%) was most abundant. To date, this is the first report revealing the essential oil components of Boesenbergia armeniaca and B. stenophylla from Sabah, Borneo.